Potential for re-emergence of wheat stem rust in the United Kingdom - Lewis, Clare M; Persoons, Antoine; Bebber, Daniel P; Kigathi, Rose N; Maintz, Jens; Findlay, Kim; Bueno-Sancho, Vanessa; Corredor-Moreno, Pilar; Harrington, Sophie A; Kangara, Ngonidzashe; Berlin, Anna; García, Richard; et al. (Communications biology, 2018)
Wheat stem rust, a devastating disease of wheat and barley caused by the fungal pathogen Puccinia graminis f. sp. tritici, was largely eradicated in Western Europe during the mid-to-late twentieth century. However, isolated outbreaks have occurred in recent years. Here we investigate whether a lack of resistance in modern European varieties, increased presence of its alternate host barberry and changes in climatic conditions could be facilitating its resurgence. We report the first wheat stem rust occurrence in the United Kingdom in nearly 60 years, with only 20% of UK wheat varieties resistant to this strain. Climate changes over the past 25 years also suggest increasingly conducive conditions for infection. Furthermore, we document the first occurrence in decades of P. graminis on barberry in the UK . Our data illustrate that wheat stem rust does occur in the UK and, when climatic conditions are conducive, could severely harm wheat and barley production.